Diversity of Cultivable Microbes From Soil of the Fildes Peninsula, Antarctica, and Their Potential Application - Cong, Bailin; Yin, Xiaofei; Deng, Aifang; Shen, Jihong; Tian, Yongqi; Wang, Shaoyun; Yang, Huanghao (Frontiers in Microbiology, 2020)
To explore the diversity and application potential of Antarctic microorganisms, 1208 strains bacteria and fungi were isolated from 5 samples collected from the Fildes Peninsula during China's 27th and 31st Antarctic expeditions. Eighty-three strains bacteria belonging to 20 genera and 30 strains fungi belonging to 7 genera were identified. Among them, 8 strains bacteria and 10 strains fungi showed low sequence similarity to the database, suggesting that they might be novel species. Physiological-biochemical characteristics showed that the identified bacteria could utilize many kinds of carbohydrates and that the identified fungi could produce several kinds of extracellular enzymes. The fungal strain MS-19, identified as Aspergillus sydowii, possesses the potential to produce antifungal activity agents based on an activity-guided approach. Further isolation yielded four polyketones: versicone A (1), versicone B (2), 4-methyl-5,6-dihydro-2H-pyran-2-one (3), and (R)-(+)-sydowic acid (4). It should be noted that 1 displayed strong activity against Candida albicans, with an MIC value of 3.91 μg/mL.